The 1874–1876 volcano-tectonic episode at Askja, North Iceland: Lateral flow revisited - Hartley, Margaret E.; Thordarson, Thor (Geochemistry, Geophysics, Geosystems, 2013)
[1] The Askja volcanic system, North Iceland, experienced a volcano-tectonic episode between 1874 and 1876, the climax of which was a rhyolitic, phreatoplinian to Plinian eruption at Askja central volcano on 28–29 March 1875. Fissure eruptions also occurred in 1875, producing the Nýjahraun lava, 45–65 km north of Askja. The Nýjahraun basalt is indistinguishable, in terms of whole-rock major elements, from the small-volume basaltic eruptions that took place at Askja in the early 20th century. It has been suggested that all of these basalts originated from a shallow magma chamber beneath Askja, with the Nýjahraun eruptions being fed by northward-propagating lateral dykes. It has also been conjectured that the Holuhraun lava, located at the southern tip of the Askja volcanic system 15–25 km south of Askja, was connected with the 1874–1876 Askja volcano-tectonic episode. We re-examine these interpretations in light of new whole-rock, glass and melt inclusion analyses from samples collected along the length of the Askja volcanic system. Glasses from Nýjahraun and the Askja 20th century eruptions are geochemically distinct. We suggest that the Askja 20th century basalts mixed with evolved melts in the crust, while the Nýjahraun magma evolved without such interactions. The Holuhraun basalt is more similar to lavas erupted on the Bárðarbunga-Veiðivötn volcanic system than to postglacial basalts from Askja, indicating that particular geochemical signatures are not necessarily confined to the tectonic or structural surface expression of single volcanic systems. This has important implications for the identification and delineation of individual volcanic systems beneath the northwest sector of Vatnajökull.